The negation in the Halcnovian lect - Dolatowski, Marek (Acta Universitatis Lodziensis. Folia Germanica, 2018)
The Halcnovian lect has been spoken in daily communication in Hałcnów, a village in the former Bielsko-Biała’s language island, until 1945. Today it is almost extinct. The lect is one of Silesian East German dialects, but it developed independently for about 500 years. Because of the former language situation in the village, also the triglossia, there are elements and constructions that may be loaned from Polish or German. In this paper, first, the story of the village is presented, a short description of the Halcnovian grammar follows. The main part of the article contains a description of all possibilities to negate in the lect, there are also listed many examples. Possible foreign influences are investigated also. The analysis shows that the Halcnovian negation was lightly, but evidently influenced by other languages and that is a proof for a long and intensive language contact in the village.